2014
DOI: 10.3389/fmicb.2013.00420
|View full text |Cite
|
Sign up to set email alerts
|

Widespread dissemination of class 1 integron components in soils and related ecosystems as revealed by cultivation-independent analysis

Abstract: Class 1 integrons contribute to the emerging problem of antibiotic resistance in human medicine by acquisition, exchange, and expression of resistance genes embedded within gene cassettes. Besides the clinical setting they were recently reported from environmental habitats and often located on plasmids and transposons, facilitating their transfer and spread within bacterial communities. In this study we aimed to provide insights into the occurrence of genes typically associated with the class 1 integrons in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 47 publications
5
48
1
Order By: Relevance
“…5) suggested an increased horizontal transfer potential of these ARGs. In particular, the potential for horizontal gene transfer would be higher when the class 1 integrons are located in the transferable IncP-1ε plasmids or other mobility elements (Heuer et al 2012;Jechalke et al 2014c;Wolters et al 2015). The class 1 integrons are also important for co-selection and mobilization of other ARGs (apart from β-lactamases), especially when selective pressure by antibiotics is present (Jechalke et al 2014c).…”
Section: Potential For Horizontal Gene Transfer Of Args In Manure-trementioning
confidence: 99%
See 3 more Smart Citations
“…5) suggested an increased horizontal transfer potential of these ARGs. In particular, the potential for horizontal gene transfer would be higher when the class 1 integrons are located in the transferable IncP-1ε plasmids or other mobility elements (Heuer et al 2012;Jechalke et al 2014c;Wolters et al 2015). The class 1 integrons are also important for co-selection and mobilization of other ARGs (apart from β-lactamases), especially when selective pressure by antibiotics is present (Jechalke et al 2014c).…”
Section: Potential For Horizontal Gene Transfer Of Args In Manure-trementioning
confidence: 99%
“…The critical roles of integrons in the dissemination of ARGs in environments have been highlighted by cultivation methods and metagenomics approaches (Hardwick et al 2008;Stalder et al 2012;Gillings et al 2015). Class 1 integrons have been extensively studied due to their widespread distribution in Gram-negative bacteria of clinical importance (Stalder et al 2012), and the intI1 genes were reported to be very common in soils and related ecosystems (Gillings et al 2008;Jechalke et al 2014c).…”
Section: Potential For Horizontal Gene Transfer Of Args In Manure-trementioning
confidence: 99%
See 2 more Smart Citations
“…We could show that the abundance of sulfonamide resistance genes (sul1, sul2) was unexpectedly lower in the rhizosphere of maize and grass grown in manure-treated soils compared to control. Another interesting observation was the enrichment of class 1 integrons and IncP-1 plasmids in the rhizosphere of lettuce grown in three soils (Jechalke et al 2014). This increased abundance might be caused by aromatic compounds in the root exudates of lettuce (Neumann et al 2014).…”
Section: Detection Of Antibiotic Resistance Genes and Mobile Genetic mentioning
confidence: 99%